The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1016/j.ejpain.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Altered pain and thermal sensation in subjects with isolated parietal and insular cortical lesions

Abstract: Studies of sensory function following cortical lesions have often included lesions which multiple cortical, white matter, and thalamic structures. We now test the hypothesis that lesions anatomically constrained to particular insular and parietal structures and their subjacent white matter are associated with different patterns of sensory loss. Sensory loss was measured by quantitative sensory testing (QST), and evaluated statistically with respect to normal values.All seven subjects with insular and/or pariet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 56 publications
1
41
1
Order By: Relevance
“…However, recent neuroanatomical work in primate models (58) along with neuroimaging results from human studies (61,62,157), have repeatedly challenged this view (67). Strong evidence has been indeed provided not only for the fact that other cortical areas than the somatosensory one could be involved in thermal processing, but that in fact these areas could play a more specific role in sub-serving temperature (as well as pain) (263) sensations in humans (19,62,237,296). Amongst these areas, the dorsal margin of the posterior insular cortex has been proposed as the specific area for the cortical processing of both the discriminative (157) and affective (62,251) components of thermal sensations in humans.…”
Section: Cortical Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent neuroanatomical work in primate models (58) along with neuroimaging results from human studies (61,62,157), have repeatedly challenged this view (67). Strong evidence has been indeed provided not only for the fact that other cortical areas than the somatosensory one could be involved in thermal processing, but that in fact these areas could play a more specific role in sub-serving temperature (as well as pain) (263) sensations in humans (19,62,237,296). Amongst these areas, the dorsal margin of the posterior insular cortex has been proposed as the specific area for the cortical processing of both the discriminative (157) and affective (62,251) components of thermal sensations in humans.…”
Section: Cortical Integrationmentioning
confidence: 99%
“…cold) (19) thermo-anesthesia in humans. For example, in a recent quantitative sensory analysis, warm and cold hypoesthesia was consistently recorded in patients with constrained cortical lesions located in the insular and parietal cortices (296). Interestingly, lesions of the human insular cortex not only induce thermosensory deficits, but also, these are very often accompanied by the development of central pain (19,296).…”
Section: Cortical Integrationmentioning
confidence: 99%
“…This has been demonstrated for patients with lesions of the spinal cord (Ducreux et al, 2006;Finnerup et al, 2003), and brain Garcia-Larrea et al, 2010). In the case of cortical lesions, the results of a recent study demonstrate warm and cold hypoesthesia based on QST thresholds in all subjects with lesions of parietal or insular cortex or both (Veldhuijzen et al, 2009). The largest degree of thermal hypoesthesia by threshold measures was found in the subject with the largest lesion, which involved extensive parietal and insular lobar lesions (see also (Greenspan et al, 1999).…”
Section: Prevalence Of Sensory Abnormalities In Central Pain?mentioning
confidence: 83%
“…A recent study has suggested that CPSP occurred only in individuals with lesions including posterior insula/retroinsula, which spare the anterior and posterior parietal cortex (Veldhuijzen et al, 2009). Evidence from neuroimaging studies suggests that the parietal lobe is involved in the mechanism of CPSP and CPSP-associated allodynia in subjects with strokes of the lateral medulla (Wallenberg syndrome) (Peyron et al, 1998), and the thalamic nucleus Vc which projects to the parietal cortex .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation